Volunteer motives as a catalyst of the social economy - Ana Todorova; Irina Kostadinova (Entrepreneurship and Sustainability Issues)
Volunteering is a catalyst for developing well-being-oriented communities, which are fundamental to the social economy. The transition towards a social economy triggers questions about volunteer roles and the forces which drive them. The paper explores volunteers' motivations, attitudes, and expectations and volunteering as a catalyst for deploying the social economy concept. A survey was conducted among the volunteer community in Bulgaria, and 422 volunteers responded. The study shows that while each person has their motivations for participating in charitable activities, volunteers stand out for their desire to develop new skills, meet new people, belong to a specific community, and change society for the better. The analysis enriches existing views by identifying effective communication as key to attracting and retaining volunteers. Organisations must clearly explain their mission, be transparent about their goals and expectations, and create an environment where volunteers feel valued for their contributions. The obtained insights complement the existing theoretical knowledge in the field of social economy, human resources and motivation. They will also stress the need to develop policies to promote civic and corporate volunteering. The need for more in-depth research in managing voluntary organisations and, more specifically, managing voluntary human resources is emphasised.